Neural Correlates of Dynamically Evolving Interpersonal Ties Predict Prosocial Behavior - Fahrenfort, Johannes J.; van Winden, Frans A.; Pelloux, Benjamin; Stallen, Mirre; Ridderinkhof, K. Richard (Frontiers in Neuroscience, 2012)
There is a growing interest for the determinants of human choice behaviour in social settings. Upon initial contact, investment choices in social settings can be inherently risky, as the degree to which the other person will reciprocate is unknown. Nevertheless, people have been shown to exhibit prosocial behaviour even in one-shot laboratory settings where all interaction has been taken away. A logical step has been to link such behaviour to trait empathy-related neurobiological networks. However, as a social interaction unfolds, the degree of uncertainty with respect to the expected payoff of choice behaviour may change as a function of the interaction. Here we attempt to capture this factor. We show that the interpersonal tie one develops with another person during interaction - rather than trait empathy - motivates investment in a public good that is shared with an anonymous interaction partner. We examined how individual differences in trait empathy and interpersonal ties modulate neural responses to imposed monetary sharing. After, but not before interaction in a public good game, sharing prompted activation of neural systems associated with reward (striatum), empathy (anterior insular cortex [AIC] and anterior cingulate cortex [ACC]) as well as altruism and social significance (posterior superior temporal sulcus [pSTS]). Although these activations could be linked to both empathy and interpersonal ties, only tie-related pSTS activation predicted prosocial behaviour during subsequent interaction, suggesting a neural substrate for keeping track of social relevance.